To assess placental volume in first and second trimester of pregnancy in UKM Medical Centre. - Vahid Bossaghzadeh,; Shuhaila Ahmad,; Norzilawati Mohd Naim,; Nor Azlin Mohd Ismail,; Rahana Abdul Rahman,; Zaleha Abdullah Mahdy, (Department of Surgery, UKM Medical Centre, 2014)
This was a prospective cohort study. From May 2011 to June 2012, pregnant women were recruited via the obstetric clinic, patient admission centre and wards in UKM Medical Centre (UKMMC). An ultrasound scan was performed at 11-16 weeks and again at 18-26 weeks of gestation to check for placental volume and Uterine Artery Resistance Index (UARI) and Pulsatility Index (UAPI). The placental volume was measured by three-dimensional ultrasound using the Virtual Organ Computer-Aided Analysis (VOCAL) technique.